The Impact of Laser Technology in Cancer Treatment - Hussam Alwan Mwaze; Nabaa Qaes Muhsen (American Journal of Botany and Bioengineering, 2025)
Lasers are a unique and powerful tool extensively used in diagnosis and therapy of several medical conditions due to their non-contact and non-ionizing behavior. Lasers are also becoming increasingly more appreciated in oncology. Besides their use in photodynamic therapy, which is their most successful clinical application in cancer treatment, lasers have established other applications including activation of the immune system to target malignancies and improvement of the delivery and effectiveness of traditional cancer therapies. Furthermore, recent technological advents have opened new perspectives for the use of lasers as a powerful instrument in oncosurgery, namely through the control of the lesion’s severity, location and extension during laser ablation surgical procedures. Presented with a laser of proper wavelength, intensity, and dose, a living tissue can show a selective light absorption, in such a way that depending on the chromophores, the temperature of the tissues can be raised enough to induce a thermally destructive effect. Lasers are revolutionizing, or have revolutionized, several important technologies and applications like real time diagnostics of machinery for preventive maintenance, optical data storage, cutting, engraving, marking, and welding of metals, polymers, or ceramic materials, measurement of distances, speeds, and levelling among others which are now important tools for modern society. In medicine, the advent of surgery with high technology lasers is expected to have a similar impact. Despite of being a recent technology, laser therapy has been used with success in several types of surgical procedures and has demonstrated a high potential for the development of new procedures and substantial improvements on traditional ones. In oncology, lasers are now starting to become an important tool for a number of different applications both in preoperative preparation procedures and in surgery, including endoscopic and precise cutting, sculpting and vaporization of malignant tissues. Due to the high flexibility in the administering of laser radiation, and to the wide availability of commercial medical laser apparatus with a large range of wavelengths, temporal emission modalities and optical fibers, laser technological improvements are expected to further change the surgical scenario of cancer treatment. Over the years, through the pioneering clinical and preclinical work of several research groups, the use of the laser for the management of cancer has been a promising therapeutic approach. Despite this, the safety and the effectiveness of the therapy is still debated and it is clear that a great deal of study is required before its introduction as a routine clinical procedure, also in consideration of the tremendous amount of possible different intervention protocols possible using laser technology.